In defence of moral error theory and moral abolitionism - Dimmock, Mark (2016)
In this thesis I present a challenge to anyone who continues to engage in moral thinking – that is to say, I present a challenge to most people currently alive. In the first three chapters, I defend the idea that no non-negative moral proposition is ever true ('Moral Error Theory'). On the back of this defence, I then provide arguments in support of the related - but not entailed – Moral Abolitionist account. According to this view, moral thought, moral talk and morally-coloured motivations should be abolished in favour of an entirely non-moral assessment of the world and the options that face us when we deliberate on questions regarding to ‘how to act’ or ‘how to live’.